2019
DOI: 10.3390/ijerph17010068
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Chronotype and Dietary Pattern among Adults: A Scoping Review

Abstract: Chronotype reflects an individual’s preferred time of the day for an activity/rest cycle and individuals can be classified as a morning, intermediate, or evening type. A growing number of studies have examined the relationship between chronotype and general health. This review aimed to map current evidence of the association between chronotype and dietary intake among the adult population. A systematic search was conducted across five databases: EBSCO Host, Medline & Ovid, Pubmed, Scopus, and The Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 95 publications
7
81
0
Order By: Relevance
“…Although studies are too limited to make firm conclusions regarding nutritional characteristics related to night eating, the available information points towards maternal night eating being generally associated with less healthy dietary intake, low diet quality and reductions in circulating levels of certain micronutrients during pregnancy. This is supported by studies in teenagers and adults, which have consistently reported that individuals with a delayed temporal distribution of food intake (i.e., night-eaters, late-eaters, an evening chronotype, night-shift workers) were mostly engaged in unhealthy eating behavior with poor diet quality [59,60,65]. Overall, it seems that diet composition among night eaters is an important aspect to consider when studying night eating and health implications.…”
Section: Nutritional Aspects Of Night Eatingmentioning
confidence: 82%
See 1 more Smart Citation
“…Although studies are too limited to make firm conclusions regarding nutritional characteristics related to night eating, the available information points towards maternal night eating being generally associated with less healthy dietary intake, low diet quality and reductions in circulating levels of certain micronutrients during pregnancy. This is supported by studies in teenagers and adults, which have consistently reported that individuals with a delayed temporal distribution of food intake (i.e., night-eaters, late-eaters, an evening chronotype, night-shift workers) were mostly engaged in unhealthy eating behavior with poor diet quality [59,60,65]. Overall, it seems that diet composition among night eaters is an important aspect to consider when studying night eating and health implications.…”
Section: Nutritional Aspects Of Night Eatingmentioning
confidence: 82%
“…In terms of micronutrients, Gontijio and colleagues [18] demonstrated that increased night-time energy intake was associated with lower intakes of dietary riboflavin, calcium and iron during pregnancy. Given that night eaters were more likely to be evening chronotypes [60], the authors further showed that pregnant women with an eveningness tendency had lower diet quality and fewer fruit intake, than those with a morningness tendency [61]. Similarly, the GUSTO research group observed that pregnant night eaters consumed lower amounts of total fruit and whole grains, and had a lower diet quality than day eaters ( Table 2).…”
Section: Nutritional Aspects Of Night Eatingmentioning
confidence: 95%
“…The size, frequency, or regularity of food behaviors are important domains to examine when studying eating behaviors [23,24], as they provide easy and convenient information with clinical significance. A dietary questionnaire modified from previous studies on dietary behaviors conducted by Stea et al [25], Sun et al [17], and Arora et al [12] was therefore adopted to capture particular dietary characteristics of school-aged children.…”
Section: Questionnaire On Dietary Characteristicsmentioning
confidence: 99%
“…A dietary questionnaire modified from previous studies on dietary behaviors conducted by Stea et al [25], Sun et al [17], and Arora et al [12] was therefore adopted to capture particular dietary characteristics of school-aged children. The dietary questionnaire covered some important aspects that have been widely assessed in previous studies: meal regularity and portions [13,15], snacking and fast food consumption [12,24], sugar intake [15,16], fruit and vegetable intake [12,[26][27][28], and television (TV) viewing during mealtimes [13,29]. Items were prepared in English and translated to Chinese for the purpose of collecting data.…”
Section: Questionnaire On Dietary Characteristicsmentioning
confidence: 99%
“…In a cross-sectional study on young adults, a higher variation in meal timing during the week was observed in evening-type subjects (33) . A review study suggested that evening-type individuals, defined as those who prefer to perform activities in the evening hours and sleep and wake up late or those who have an eveningness preference, are most likely to have unhealthy dietary habits (45) . Therefore, the association between greater day-to-day variations in energy intake and lower diet quality observed in the present study can be attributed to chronotype.…”
Section: Discussionmentioning
confidence: 99%